PERANCANGAN WEB KOMIK “KUPAS (KULINER PASAR)” SEBAGAI PELESTARIAN TENTANG MAKANAN TRADISIONAL - Rahmaputri, Selly; Pratiwi, Wilsa (Anggada : Jurnal Desain dan Seni, 2021)
Traditional Food is a part of Culture of Region. Each food cultures mades specific characteristics to difference of each one to another region. Jakarta, as a capital city of Indonesia, many citizen from outside the city came here to change their future, and Jakarta has every food options to offers. Modern Food is one of the easiest to find food for them such as Varieties of milk tea, Boba tea or Thai tea, Mango cream Juice, Salted Egg fusion foods, etc. This Modern food slowly replaces the authentic Traditional Jakarta’s foods to its existence such as Kerak Telor, Kue Cincin, Roti Gambang, Es Goyang, etc.Public awareness to holds the importance value of Jakarta’s Traditional food is in minimal. Advertisement of modern food is easily to find in Social Media now a day and this mades the Jakarta’s Traditional Foods spotlight fades slowly. Therefore, to gain the spotlight for Jakarta’s Traditional food back to its track, The Millenials uses virtual media as a tool for them to promote the message of the importance value for traditional culinary. They use a web comic with amazing visuals and on point messages as a virtual approach to millennials to attract their attention as the majority of them tends to read and look up for informations from their gadgets then books for practical uses.